Effect of different mucosa thickness and resiliency on stress distribution of implant-retained overdentures-2D FEA - Ricardo Barao, Valentim Adelino [UNESP]; Assunção, Wirley Goncalves [UNESP]; Tabata, Lucas Fernando [UNESP]; Sousa, Edson Antonio Capello [UNESP]; Rocha, Eduardo Passos [UNESP] (Elsevier B.V., 2008)
The study aimed to evaluate the effect of different mucosa thickness and resiliency on stress distribution of implant-retained overdentures using a two-dimensional finite element analysis. Models were used in order to simulate two situations. In group A, model represented an edentulous mandible supporting an overdenture retained by two-splinted-implants connected with bar-clip system while in group B, model simulated an edentulous mandible supporting an overdenture retained by two-splinted-implants connected with bar-clip system associated with two-distally placed o'ring system. In each group, mucosa assumed three characteristics of thickness (1, 3 and 5 mm) in the resiliencies: hard, resilient and soft, respectively Evaluation was performed on Ansys software. Group A showed higher stress values regardless of the mucosa characteristics. Overall, stress decreased at the supporting tissues as mucosa. thickness and resiliency increased. Regarding supporting tissues, cortical bone showed the highest stress values. The use of bar-clip attachment system with distally placed o'ring attachment design optimized the stress distribution. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Dental implants; Overdenture; Attachment; Finite element analysis; Biomechanics